Solid-state battery and preparation method thereof
By using fluorine-containing adhesives in the sulfide electrolyte membrane of solid-state batteries and performing surface modification, the problem that electrolyte membrane in solid-state batteries is difficult to take into account both high ionic conductivity and mechanical strength, which significantly improves the cycle life of the battery and performance.
Patent Information
- Application Number
- CN202411614273.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-12
AI Technical Summary
The sulfide solid electrolyte membrane in existing solid-state batteries is difficult to take into account high ionic conductivity and high mechanical strength, which leads to the battery being easily broken and short-circuited during charging and discharging, affecting the cycle life.
The fluorine-containing monomer, dimer and polymer are used as the binder, and the surface modification treatment is used to make the molar ratio of carbon element to fluorine element on the surface of the binder between 0.41 and 1 to enhance the adhesive. The adhesion and tensile resistance of the caking agent can improve the mechanical strength and ionic conductivity of the solid electrolyte membrane.
Through the use of modified binders, the mechanical strength and ionic conductivity of the solid electrolyte membrane have been significantly improved, effectively solving the problems of battery rupture and short circuit during charging and discharging, and extending the service life and cycling performance of the solid-state battery.
Smart Images

Figure CN119481249A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of secondary batteries, and in particular to a solid-state battery and a preparation method thereof. Background Art
[0002] All-solid-state batteries use non-flammable solid electrolyte membranes instead of organic liquid electrolytes and polymer separators, which can simplify battery design, improve battery safety and energy density, and widen the battery's operating temperature range. Oxides, sulfides and polymer electrolytes are the main materials in solid electrolyte membranes. Among them, sulfide electrolytes have attracted much attention due to their high ionic conductivity, low Young's modulus, and easy large-scale processing. In particular, solid electrolyte membranes with sulfide electrolytes as the main material can make the energy density of solid-state batteries reach more than 500Wh / kg when matched with high-capacity positive and negative electrodes, and are expected to become one of the important power sources in the future.
[0003] The presence of binders in solid electrolyte membranes will cause the ionic conductivity of solid electrolyte membranes to be lower than that of sulfide electrolyte materials, and as the percentage of binders in solid electrolyte membranes increases, the attenuation of ionic conductivity of solid electrolyte membranes becomes more obvious. In order to maintain the high ionic conductivity of solid electrolyte membranes, the percentage of binders in solid electrolyte membranes must be kept below 10%. However, a low content of binders can easily lead to poor mechanical strength of solid electrolyte membranes, which can easily cause uneven stress on the electrolyte membrane during assembly or charge and discharge cycles, causing battery short circuits, thereby affecting the cycle life of all-solid-state batteries.
[0004] Therefore, it is necessary to design a solid-state battery and a preparation method thereof to solve the above problems. Summary of the invention
[0005] In view of the above shortcomings of the prior art, the present invention provides a solid-state battery and a preparation method thereof, which are used to improve the technical problem that the sulfide solid electrolyte membrane in the existing solid-state battery is difficult to achieve both high ionic conductivity and high mechanical strength.
[0006] To achieve the above-mentioned purpose and other related purposes, the present invention provides a solid-state battery, which includes a solid electrolyte membrane, wherein the solid electrolyte membrane includes a sulfide electrolyte and a binder, wherein the binder includes at least one of a fluorine-containing monomer, dimer, or polymer, and the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41 to 1.
[0007] In an example of the present invention, the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41-0.88.
[0008] In an example of the present invention, the thickness of the solid electrolyte membrane is 30-60 μm.
[0009] In an example of the present invention, the binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene copolymer and ethylene-tetrafluoroethylene copolymer.
[0010] In an example of the present invention, the mass of the sulfide electrolyte is 90% to 99.5% of the mass of the solid electrolyte membrane; the mass of the binder is 0.5% to 10% of the mass of the solid electrolyte membrane.
[0011] In one example of the present invention, the ionic conductivity of the sulfide electrolyte is greater than 1 mS / cm.
[0012] In an example of the present invention, the particle size of the sulfide electrolyte is 1-10 μm.
[0013] In one example of the present invention, the sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Br, Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 At least one of .
[0014] The present invention also provides a method for preparing the solid-state battery described in any of the above examples, the method comprising providing a positive electrode sheet, a solid electrolyte membrane and a negative electrode sheet; assembling the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet into a battery cell, and encapsulating the battery cell to obtain a solid-state battery;
[0015] Wherein, the preparation method of the solid electrolyte membrane comprises:
[0016] Providing a sulfide electrolyte and a binder, wherein the binder includes at least one of a monomer, a dimer, and a polymer containing fluorine;
[0017] Modifying the surface of the binder so that the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41 to 1;
[0018] The sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane.
[0019] In one example of the present invention, the surface of the binder is modified, including: plasma etching the surface of the binder to remove fluorine atoms on the surface of the binder and generate free radicals; exposing the binder to a doping source gas to allow the doping elements in the doping source gas to combine with the free radicals on the surface of the binder to form active groups; the doping elements include nitrogen and / or oxygen.
[0020] In one example of the present invention, the sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane, including: using wet coating or dry extrusion to mix the sulfide electrolyte and the binder to form a solid electrolyte membrane; wherein the mass ratio of the sulfide electrolyte to the binder is (90-99.5):(0.5-10).
[0021] The present invention provides a solid-state battery, wherein the solid electrolyte membrane assembled in the solid-state battery comprises a sulfide electrolyte and a fluorine-containing binder, wherein the fluorine-containing binder in the solid electrolyte membrane has a large number of surface active groups after surface treatment, which can improve the transmission performance of the binder for lithium ions, and further enhance the adhesion and tensile strength of the binder. In summary, the solid electrolyte membrane using the same content of modified binder has higher mechanical strength and ionic conductivity, which can effectively solve the problem of electrolyte membrane rupture and battery short circuit caused by electrode volume change during the charge and discharge process of the solid-state battery, and enhance the service life and cycle performance of the solid-state battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only some embodiments of the present invention. For ordinary technicians in this field, other embodiments can be obtained based on these drawings without paying creative work.
[0023] Figure 1 Schematic diagram of a process for preparing a solid electrolyte in one embodiment of the present invention;
[0024] Figure 2 FIG. 1 is a flow chart of step S2 in an embodiment of the present invention. DETAILED DESCRIPTION
[0025] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0026] In the present invention, it should be noted that the terms “first” and “second” are only used for description and distinction purposes and cannot be understood as indicating or implying relative importance.
[0027] The present invention provides a solid-state battery, which is a solid-state lithium-ion secondary battery. The solid-state battery comprises a positive electrode sheet, a negative electrode sheet and a solid electrolyte membrane, wherein the solid electrolyte membrane is arranged between the positive electrode sheet and the negative electrode sheet to separate the positive electrode sheet and the negative electrode sheet, and serves as a lithium ion conductor between the positive electrode sheet and the negative electrode sheet.
[0028] The solid electrolyte membrane includes a sulfide electrolyte and a binder, wherein the binder includes at least one of a fluorine-containing monomer, dimer, and polymer. The binder is a surface-modified fluorine-containing binder, wherein the fluorine atoms (F) on the surface of the binder are modified and removed and replaced with other doping atoms, so that the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41 to 1.
[0029] Specifically, some fluorine atoms on the surface of the binder are modified and removed to generate free radicals. The free radicals on the surface of the binder form new active groups under the doping of other elements (such as O, N, etc.). The active groups on the surface of the binder effectively increase the surface free energy of the binder, and improve the adhesion and tensile strength of the binder. At the same time, the doped atoms with low electronegativity on the surface of the binder have strong electron-withdrawing properties, so that the binder and the lithium ions in the sulfide electrolyte can migrate under the ion-dipole interaction, thereby improving the lithium ion conductivity of the solid electrolyte membrane. Therefore, the solid electrolyte membrane using the same content of modified binder has higher mechanical strength and ionic conductivity.
[0030] Among them, the molar ratio of carbon element (C) to fluorine element (F) on the surface of the binder is 0.41 to 1, for example, the C / F molar ratio on the surface of the binder can be 0.41, 0.56, 0.59, 0.60, 0.65, 0.68, 0.7, 0.75, 0.8, 0.85, 0.88, 0.89, 0.9, 0.95 or 1. When the C / F molar ratio on the surface of the binder is within the above-mentioned suitable range, the ionic conductivity and mechanical strength of the solid electrolyte membrane can be optimized. If the C / F molar ratio on the surface of the binder is too low, the improvement effect of the binder on lithium electron conductivity and mechanical strength will not be obvious; if the C / F molar ratio on the surface of the binder is too high, the surface of the binder will be too rough and difficult to fiberize, resulting in a decrease in the mechanical strength of the solid electrolyte membrane.
[0031] In some embodiments, the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41-0.88, for example, the C / F molar ratio on the surface of the binder can be 0.41, 0.45, 0.47, 0.5, 0.53, 0.56, 0.59, 0.6, 0.63, 0.65, 0.68, 0.7, 0.75, 0.8, 0.83, 0.85 or 0.88. Optionally, the molar ratio of carbon element to fluorine element on the surface of the binder is 0.56-0.75, for example, the C / F molar ratio on the surface of the binder can be 0.56, 0.6, 0.63, 0.65, 0.67, 0.7, 0.73 or 0.75.
[0032] In some embodiments, the mass of the sulfide electrolyte is 90% to 99.5% of the mass of the solid electrolyte membrane, and correspondingly, the mass of the binder is 0.5% to 10% of the mass of the solid electrolyte membrane. For example, the mass content of the binder in the solid electrolyte membrane can be 0.5%, 0.8%, 1%, 1.5%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. Optionally, the mass content of the binder in the solid electrolyte membrane can be 0.5% or 1%. When the mass content of the binder in the solid electrolyte membrane is within the above range, the solid electrolyte membrane can have both good ionic conductivity and mechanical strength. If the mass content of the binder in the solid electrolyte membrane is too low, the solid electrolyte membrane will be close to powder, and the film forming property will be poor or even difficult to form; if the mass content of the binder in the solid electrolyte membrane is too high, the ionic conductivity of the solid electrolyte membrane will be too low, and it will be difficult to conduct lithium ions.
[0033] In some embodiments, the thickness of the solid electrolyte membrane is 30-60 μm, for example, the thickness of the solid electrolyte membrane may be 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm or 60 μm. Optionally, the thickness of the solid electrolyte membrane may be 40 μm.
[0034] In some embodiments, the particle size of the sulfide electrolyte is 1-10 μm, and the ionic conductivity of the sulfide electrolyte is greater than 1 mS / cm.
[0035] In some embodiments, the sulfide electrolyte is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Br, Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 At least one of the above. That is, the sulfide electrolyte can be any one of the above-mentioned types, for example, Li3PS4, Li7P3S11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Cl, Li6PS5Br or Li 5.5 PS 4.5 Cl 1.5 Optionally, the sulfide electrolyte is Li 5.5 PS 4.5 Cl 1.5 The sulfide electrolyte may also be any combination of the above-mentioned types, for example, Li3PS4 and Li7P3S 11 The composition of Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 GeP2S 12 and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 SnP2S 12 and Li 5.5 PS 4.5 Cl 1.5 The composition of Li6PS5Br and Li 5.5 PS 4.5 Cl 1.5 The composition of Li 10 SnP2S 12 , Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 It should be noted that when the sulfide electrolyte is a composition, there is no restriction on the ratio between the components in the composition, and they can be mixed in any ratio.
[0036] In some embodiments, the binder includes at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and ethylene-tetrafluoroethylene copolymer (ETFE) with a surface C / F molar ratio of 0.41 to 1. That is, the binder can be any one of the types listed above, for example, it can be PTFE, PVDF, ETFE, PVDF-HFP or PVDF-HFE. Optionally, the binder is PTFE; the binder can also be any combination of the types listed above, for example, it can be a combination of PTFE and PVDF, or a combination of PTFE and PVDF-HFP, or a combination of PTFE and PVDF-HFE, or a combination of ETFE and PVDF, or a combination of PTFE, PVDF and PVDF-HFP, or a combination of PTFE, PVDF and PVDF-HFE. It should be noted that when the binder is a composition, there is no restriction on the ratio between the components in the composition, and it can be mixed in any proportion.
[0037] In some embodiments, the positive electrode sheet includes a positive current collector and a positive active material layer coated on at least one side of the positive current collector, the positive active material layer includes a positive electrode material, a positive electrode binder, a positive electrode conductive agent and a solid electrolyte, and the solid electrolyte is a sulfide electrolyte used in a solid electrolyte membrane. The mass ratio of the positive electrode active material, the solid electrolyte, the positive electrode binder and the positive electrode conductive agent can be (50-75): (20-50): (0-3): (1-3).
[0038] Among them, the positive electrode current collector can adopt foil with good conductivity and mechanical strength, such as aluminum, nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon; in addition to foil, the positive electrode current collector can also adopt any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0039] The positive electrode material may be a layered positive electrode material, an olivine positive electrode material or a spinel positive electrode material. The layered positive electrode material may be lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (NCM) or lithium nickel cobalt aluminum oxide (NCA), etc.; the olivine positive electrode material may be lithium iron phosphate (LFP), lithium iron manganese phosphate (LFMP), etc.; the spinel positive electrode material may be lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO), lithium-rich manganese-based oxide (LRMO), etc.
[0040] The positive electrode binder is, for example, selected from one or more combinations of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), and styrene-butadiene rubber (SBR).
[0041] The positive electrode conductive agent is, for example, one selected from carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc., or a combination of two or more selected from the group consisting of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc., in any proportion.
[0042] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer coated on at least one side of the negative electrode current collector, the negative electrode active material layer includes a negative electrode material, a solid electrolyte, a negative electrode binder, and a negative electrode conductive agent, and the solid electrolyte is a sulfide electrolyte used in a solid electrolyte membrane. The mass ratio of the negative electrode active material, the solid electrolyte, the negative electrode binder, and the negative electrode conductive agent can be (50-75): (20-50): (0-3): (1-3).
[0043] Among them, the negative electrode current collector can be made of foil with good conductivity and mechanical strength, such as aluminum, nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon; in addition to foil, the negative electrode current collector can also be in any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric.
[0044] The negative electrode active material is selected from one or more of tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxides, silicon carbon compounds, and nano metal oxides (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles).
[0045] The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers, or a combination of two or more of the two selected from the group consisting of carbon black, acetylene black, graphene, carbon nanotubes, and carbon nanofibers in any proportion.
[0046] The negative electrode binder is selected from any one of fluoroethylene-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR), or a combination thereof mixed in any proportion.
[0047] In other embodiments, the negative electrode plate can be a metal lithium plate, a metal indium plate, or a lithium-containing alloy plate (such as a lithium-tin-indium alloy plate, a lithium-silicon alloy plate, a lithium-tin alloy plate, or a lithium-aluminum alloy plate). For example, in one example, the negative electrode plate is selected from a metal lithium plate.
[0048] On the other hand, the present invention also provides a method for preparing a solid-state battery, which comprises: providing a positive electrode sheet, a solid electrolyte membrane and a negative electrode sheet; assembling the positive electrode sheet, the solid electrolyte membrane and the negative electrode sheet into a battery cell, and encapsulating the battery cell to obtain a solid-state battery.
[0049] like Figure 1 As shown, the method for preparing the solid electrolyte membrane in the above solid-state battery comprises the following steps:
[0050] S1. Providing a sulfide electrolyte and a binder; the binder comprises at least one of a fluorine-containing monomer, dimer, and polymer;
[0051] S2, performing surface modification on the binder so that the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41 to 1;
[0052] S3, mixing the sulfide electrolyte and the binder to form a solid electrolyte membrane.
[0053] In some embodiments, the sulfide electrolyte provided in step S1 is selected from Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Br, Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 One or more; Optionally, the sulfide electrolyte is selected from Li 5.5 PS 4.5 Cl 1.5 The particle size of the sulfide electrolyte selected in step S11 is 1-10 μm, and the ion conductivity is greater than 1 mS / cm.
[0054] In some embodiments, the binder provided in step S1 is selected from at least one of polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFE), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP) and ethylene-tetrafluoroethylene copolymer (ETFE).
[0055] like Figure 2 As shown, in some embodiments, step S2 includes the following steps:
[0056] S21, performing plasma etching on the surface of the binder to remove fluorine atoms on the surface of the binder and generate free radicals;
[0057] S22, exposing the binder to a doping source gas, so that the doping elements in the doping source gas combine with free radicals on the surface of the binder to form active groups; the doping elements include nitrogen and / or oxygen.
[0058] Specifically, in step S21, the binder is placed in a cavity of a plasma etching device, and the binder in the cavity is plasma etched to remove fluorine atoms on the surface of the binder and generate free radicals, thereby inducing a cross-linking reaction or forming unsaturated bonds on the surface; and by modulating parameters such as the atmosphere of the plasma etching device, the applied plasma power, the etching time, and the gas flow rate, the C / F molar ratio on the surface of the binder is controlled to be any value between 0.41 and 1.
[0059] In step S21, the gas used for plasma etching is one or a mixture of argon, helium, nitrogen, oxygen, hydrogen, and ammonia. Optionally, the gas used for plasma etching is oxygen. The plasma power applied for plasma etching is 10 to 200 W; the etching time for plasma etching is 10 to 1800 s; and the gas flow rate for plasma etching is 0 to 300 ml / min.
[0060] Among them, by regulating the parameters such as the plasma applied power, etching time and gas flow rate in plasma etching, the C / F molar ratio on the binder surface can be controlled. When the plasma applied power of plasma etching is small, the etching time is short, and the gas flow rate is small, the C / F molar ratio on the binder surface does not increase significantly, the adhesion of the binder is not improved significantly, and the mechanical strength of the prepared solid electrolyte membrane is limited; when the plasma applied power of plasma etching is high, the etching time is long, and the gas flow rate is large, the C / F molar ratio on the binder surface is higher than 1. At this time, the binder surface is rough, which is not conducive to subsequent fiberization, and the mechanical strength of the prepared solid electrolyte membrane also begins to decrease. Therefore, in step S21, by regulating the parameters such as the plasma applied power, etching time and gas flow rate in plasma etching, the C / F molar ratio on the binder surface is limited to 0.41~1 to ensure the improvement of the mechanical strength and ionic conductivity of the prepared solid electrolyte membrane.
[0061] Specifically, in step S22, the binder powder after plasma etching is placed in the air for 1 to 10 hours. After the binder is exposed to the air, the surface unsaturated bonds react with doping source gases such as oxygen and nitrogen, thereby introducing O and / or N elements and generating new active groups, increasing the surface free energy of the fluorine-containing binder, and thereby improving the adhesion, tensile strength and migration ability of the binder for lithium ions.
[0062] In step S3, the sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane by wet coating or dry extrusion; wherein the mixing mass ratio of the sulfide electrolyte to the binder is (90-99.5):(0.5-10).
[0063] In one example, step S3 uses a wet coating method to prepare a solid electrolyte membrane, and step S3 includes the following steps: mixing a sulfide electrolyte and a modified binder in a low-polarity solvent in a mass ratio of (90-99.5): (0.5-10), adjusting the solid content of the slurry and vacuum-treating the slurry using a vacuum degassing machine to obtain a uniform mixed slurry; using a sprayer or a coating machine to coat the mixed slurry on the surface of the substrate, drying and removing the solvent in the coating on the substrate to obtain a solid electrolyte coating, and peeling the solid electrolyte coating from the substrate to obtain a solid electrolyte membrane. Among them, the low-polarity solvent is a solvent with a polarity index lower than 2.5, for example, the first solvent is selected from at least one of toluene, xylene, n-pentane, hexane and cyclohexane; optionally, the low-polarity solvent is selected from xylene. The substrate is selected from one of aluminum foil, copper foil, PET board, release paperboard, PTFE board, and glass board.
[0064] In another example, step S3 uses a dry extrusion method to prepare a solid electrolyte membrane, and step S3 includes the following steps: uniformly mixing a sulfide electrolyte and a modified binder in a mass ratio of (90-99.5): (0.5-10) to obtain a mixed powder; placing the mixed powder at a preset temperature and repeatedly rolling it for a preset rolling time to obtain a solid electrolyte membrane. The preset temperature is 60-100°C, and the preset rolling time is 30-120 minutes.
[0065] It should be noted that the positive electrode sheet, negative electrode sheet and solid-state battery assembly process in the solid-state battery can be prepared by conventional methods in the art.
[0066] In some embodiments, the positive electrode sheet preparation process is as follows: the positive electrode material, solid electrolyte, positive electrode binder, and positive electrode conductive agent are mixed in a mass ratio of (50-75): (20-50): (0-3): (1-3), and a solvent N-methylpyrrolidone (NMP) is added to adjust the slurry solid content to 55%, and then the mixture is fully stirred and mixed under vacuum to obtain a positive electrode slurry. The positive electrode slurry is evenly coated on the positive electrode current collector, and then the positive electrode current collector is dried at room temperature and transferred to an oven for drying, and then cold pressed and cut to obtain a positive electrode sheet.
[0067] Among them, the positive electrode current collector can be made of foil with good conductivity and mechanical strength, such as aluminum, nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon; in addition to foil, the positive electrode current collector can also be in the form of film, mesh, porous, foam or non-woven fabric, etc. Any one or more combinations of various forms. The solid electrolyte is the same sulfide electrolyte used in the solid electrolyte membrane. The positive electrode material is, for example, selected from one or more combinations of lithium cobalt oxide (LCO), lithium nickel cobalt manganese oxide (NCM), lithium nickel cobalt aluminum oxide (NCA), lithium iron phosphate (LFP), lithium iron manganese phosphate (LFMP) lithium manganese oxide (LMO), lithium nickel manganese oxide (LNMO) and lithium rich manganese-based oxide (LRMO). The positive electrode binder is selected from, for example, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polyacrylonitrile (PAN), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR) or one or more combinations thereof. The positive electrode conductive agent is selected from, for example, one of carbon black, Ketjen black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, porous carbon, etc., or a combination of two or more thereof mixed in any proportion.
[0068] In some embodiments, the negative electrode sheet preparation process is as follows: the negative electrode material, solid electrolyte, negative electrode binder, and negative electrode conductive agent are mixed in a mass ratio of (50-75):(20-50):(0-3):(1-3), deionized water is added, and the solid content of the slurry is adjusted to 55%, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode collector; after drying at room temperature, the mixture is transferred to an oven for drying, and then the negative electrode sheet is obtained through cold pressing, slitting and other processes.
[0069] Among them, the negative electrode current collector can be made of foil with good conductivity and mechanical strength, such as aluminum, nickel, titanium, gold, silver, chromium, molybdenum, copper, stainless steel or carbon; in addition to foil, the negative electrode current collector can also be any one or more combinations of various forms such as film, mesh, porous, foam or non-woven fabric. The solid electrolyte is the same sulfide electrolyte used in the solid electrolyte membrane. The negative electrode active material is selected from tin, artificial graphite (single crystal graphite, polycrystalline graphite, pyrolytic graphite, graphite fiber, etc.), natural graphite (block graphite, flake graphite, earthy graphite, etc.), soft carbon, hard carbon, pure silicon (crystalline silicon, amorphous silicon or organic silicon), silicon oxide, silicon carbon compound, nano metal oxide (Fe2O3, CuO, SnO2, Mn3O4 nanoparticles). The negative electrode conductive agent is selected from one of carbon black, acetylene black, graphene, carbon nanotubes, carbon nanofibers, or a combination of two or more of them mixed in any proportion. The negative electrode binder is selected from any one of fluoroethylene-hexafluoropropylene (PVDF-HFP), polyethylene oxide (PEO), polymethyl methacrylate (PMMA), nitrile rubber (NBR), hydrogenated nitrile rubber (HNBR), styrene butadiene rubber (SBR), or a combination thereof mixed in any proportion.
[0070] In other embodiments, a metal lithium sheet, a metal indium sheet, or a lithium-containing alloy sheet (such as a lithium-tin-indium alloy sheet, a lithium-silicon alloy sheet, a lithium-tin alloy sheet, or a lithium-aluminum alloy sheet) is used as the negative electrode sheet.
[0071] The following is an example description of the assembly method of the secondary battery: integrating the positive electrode sheet on one side of the solid electrolyte membrane, for example, placing the solid electrolyte membrane on the positive electrode active material layer of the positive electrode sheet, and pressing the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 200 MPa; and then integrating the negative electrode sheet on the other side of the solid electrolyte membrane, for example, placing the negative electrode sheet on the other side of the solid electrolyte membrane, so that the negative electrode active material layer of the negative electrode sheet is in contact with the solid electrolyte membrane, and pressing the negative electrode sheet, the solid electrolyte membrane and the positive electrode sheet into one at a pressure of 200 MPa; after sealing and packaging the pressed battery cell under vacuum or inert atmosphere, a solid-state lithium-ion battery can be obtained.
[0072] The technical scheme of the present invention is described in detail below through several specific examples and comparative examples. Unless otherwise specified, the raw materials and reagents used in the following examples are commercially available products or can be prepared by conventional methods in the art.
[0073] Example 1
[0074] This embodiment provides a solid-state battery, wherein the solid electrolyte membrane assembled in the solid-state battery comprises a sulfide electrolyte with a mass content of 99% and a modified binder with a mass content of 1%, wherein the sulfide electrolyte is Li 5.5 PS4.5 Cl 1.5 The binder is PTFE with a surface C / F molar ratio of 0.41.
[0075] The solid electrolyte membrane preparation process is as follows:
[0076] S1, provide sulfide electrolyte Li 5.5 PS 4.5 Cl 1.5 and binder PTFE;
[0077] S2, placing the binder powder into the cavity of the plasma etching equipment, performing plasma etching on the binder in the cavity, setting the plasma applied power to 50W, treating in an argon atmosphere for 50s, and introducing a gas flow rate of 150ml / min into the cavity; placing the etched binder powder in the air for 1 hour to obtain a surface-modified binder;
[0078] S3. Grind and mix the sulfide electrolyte and the modified binder in a mass ratio of 99:1 for 5 minutes, and roll them at 80°C, gradually narrowing the roller gap to 40 μm, and repeatedly rolling for 60 minutes at this roller gap to obtain a solid electrolyte membrane with a thickness of 40 μm.
[0079] The preparation process of the solid-state battery is as follows:
[0080] (1) Preparation of positive electrode sheet: The positive electrode material, solid electrolyte, positive electrode binder, and positive electrode conductive agent were ground and mixed at a mass ratio of 75:23:1:1 for 5 minutes to obtain a positive electrode slurry. The positive electrode slurry was placed at 80°C for roller pressing, and the roller gap was gradually reduced to 40μm. After repeated rolling at this roller gap for 60 minutes, a positive electrode active material layer with a thickness of 40μm was obtained. The positive electrode active material layer was transferred to the positive electrode current collector aluminum foil to obtain a positive electrode sheet. Among them, the positive electrode material is LiNi coated with LiNbO3. 0.9 Co 0.05 Mn 0.05 O2; the solid electrolyte adopts the same sulfide electrolyte as the solid electrolyte membrane; the positive electrode binder adopts the same modified binder as the solid electrolyte membrane; the positive electrode conductive agent adopts conductive carbon black.
[0081] (2) Preparation of negative electrode sheet: After mixing the negative electrode material, solid electrolyte, negative electrode binder, and negative electrode conductive agent in a mass ratio of 75:23:1:1, xylene is added to adjust the solid content of the slurry to 55%, and then the mixture is fully stirred and mixed under the action of a vacuum mixer to obtain a negative electrode slurry; the negative electrode slurry is evenly coated on the negative electrode current collector copper foil; after drying at room temperature, it is transferred to an oven for drying, and then cold pressed, cut, and other processes are performed to obtain a negative electrode sheet. Among them, the negative electrode material is silicon; the solid electrolyte uses the same sulfide electrolyte as the solid electrolyte membrane; the negative electrode binder uses the same modified binder as the solid electrolyte membrane; and the negative electrode conductive agent uses conductive carbon black.
[0082] (3) Assembly of solid-state batteries:
[0083] The solid electrolyte membrane and the positive electrode plate are stacked together, and a pressure of 200Mpa is applied to them to press the positive electrode plate and the solid electrolyte membrane into one; then the negative electrode plate is stacked on the side of the solid electrolyte membrane away from the positive electrode plate, and a pressure of 200Mpa is applied to it, and the positive electrode plate, the solid electrolyte membrane and the negative electrode plate are pressed together to obtain a battery cell; after the battery cell is sealed under vacuum or inert atmosphere, it is formed, divided and aged to obtain a solid-state battery.
[0084] Example 2
[0085] This embodiment provides a solid-state battery of the same system as that of Embodiment 1. The difference between this embodiment and Embodiment 1 is that in step S2 of preparing the solid electrolyte membrane, the time for introducing gas into the chamber during plasma etching is set to 300s, so that the C / F molar ratio of the binder surface is 0.56.
[0086] Example 3
[0087] This embodiment provides a solid-state battery of the same system as that of Embodiment 2. The difference between this embodiment and Embodiment 2 is that in step S2 of preparing the solid electrolyte membrane, the applied power of plasma etching is set to 100 W, so that the C / F molar ratio of the binder surface is 0.60.
[0088] Example 4
[0089] This embodiment provides a solid-state battery of the same system as that of Embodiment 2. The difference between this embodiment and Embodiment 2 is that in step S2 of preparing the solid electrolyte membrane, the applied power of plasma etching is set to 200 W, so that the C / F molar ratio of the binder surface is 0.68.
[0090] Example 5
[0091] This embodiment provides a solid-state battery of the same system as that of Embodiment 3. The difference between this embodiment and Embodiment 3 is that in step S2 of preparing the solid electrolyte membrane, the etching time of plasma etching is set to 600s, so that the C / F molar ratio of the binder surface is 0.65.
[0092] Example 6
[0093] This embodiment provides a solid-state battery of the same system as that of Embodiment 3. The difference between this embodiment and Embodiment 3 is that in step S2 of preparing the solid electrolyte membrane, the etching time of plasma etching is set to 900s, so that the C / F molar ratio of the binder surface is 0.75.
[0094] Example 7
[0095] This embodiment provides a solid-state battery of the same system as that of Embodiment 3. The difference between this embodiment and Embodiment 3 is that in step S2 of preparing the solid electrolyte membrane, the etching time of plasma etching is set to 1800s, so that the C / F molar ratio of the binder surface is 0.89.
[0096] Example 8
[0097] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that in step S2 of preparing the solid electrolyte membrane, the gas flow rate in the chamber during the plasma etching process is set to 50 ml / min, so that the C / F molar ratio of the binder surface is 0.59.
[0098] Example 9
[0099] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that in step S2 of preparing the solid electrolyte membrane, the gas flow rate in the chamber during the plasma etching process is set to 300 ml / min, so that the C / F molar ratio on the surface of the binder is 0.88.
[0100] Example 10
[0101] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that in step S3 of preparing the solid electrolyte membrane, the mass ratio of the sulfide electrolyte to the modified binder is adjusted to 99.5:0.5.
[0102] Embodiment 11
[0103] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that in step S3 of preparing the solid electrolyte membrane, the mass ratio of the sulfide electrolyte to the modified binder is adjusted to 95:5.
[0104] Example 12
[0105] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that in step S3 of preparing the solid electrolyte membrane, the mass ratio of the sulfide electrolyte to the modified binder is adjusted to 90:10.
[0106] Example 13
[0107] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that:
[0108] In the process of preparing the solid electrolyte membrane, PVDF-HFP is used as a binder in the solid electrolyte membrane; the sulfide electrolyte and the modified binder are mixed into xylene in a mass ratio of 98:2, and the solid content of the slurry is adjusted to obtain a uniform mixed slurry; the mixed slurry is coated on release paper by a sprayer or a coater, and after vacuum drying at a temperature of 60°C, the solid electrolyte coating is peeled off from the substrate to obtain a solid electrolyte membrane.
[0109] In the process of preparing the positive electrode sheet, the positive electrode material, solid electrolyte, negative electrode binder and negative electrode conductive agent are mixed in a mass ratio of 75:23:1:1, and xylene is added to adjust the solid content of the slurry to 55%, and then the positive electrode slurry is fully stirred and mixed under the action of a vacuum mixer; the positive electrode slurry is evenly coated on the positive electrode collector aluminum foil; after drying at room temperature, it is transferred to an oven for drying, and then the positive electrode sheet is obtained through cold pressing, slitting and other processes.
[0110] Embodiment 14
[0111] This embodiment provides a solid-state battery of the same system as that of Embodiment 6. The difference between this embodiment and Embodiment 6 is that the sulfide electrolyte in the positive electrode plate, the negative electrode plate and the solid electrolyte membrane is adjusted to Li6PS5Cl.
[0112] Comparative Example 1
[0113] This comparative example provides a solid-state battery of the same system as that of Example 6. The difference between this example and Example 6 is that the binder in the solid electrolyte membrane uses PTFE without surface modification.
[0114] Comparative Example 2
[0115] This comparative example provides a solid-state battery of the same system as Example 6. The difference between this example and Example 6 is that in step S2 of preparing the solid electrolyte membrane, the applied power of plasma etching is set to 250 W, the etching time is set to 1500 s, the gas flow rate into the cavity is set to 300 ml / min, so that the C / F molar ratio of the binder surface is 1.17.
[0116] Comparative Example 3
[0117] This comparative example provides a solid-state battery of the same system as Example 6. The difference between this example and Example 6 is that in step S3 of preparing the solid electrolyte membrane, the mass ratio of the sulfide electrolyte to the modified binder is adjusted to 99.9:0.1.
[0118] Comparative Example 4
[0119] This comparative example provides a solid-state battery of the same system as that of Example 6. The difference between this example and Example 6 is that in step S3 of preparing the solid electrolyte membrane, the mass ratio of the sulfide electrolyte to the modified binder is adjusted to 70:30.
[0120] To further verify the efficacy of the present invention, the mechanical strength and ionic conductivity of the solid electrolyte membranes prepared in Examples 1 to 14 and Comparative Examples 1 to 4 were first tested, and the test results are shown in Table 1. Then, the cycle life of the solid-state batteries prepared in Examples 1 to 14 and Comparative Examples 1 to 4 was tested, and the test results are shown in Table 2. The test process is as follows:
[0121] 1. Test of C / F molar ratio on adhesive surface: Take a small amount of adhesive powder of the embodiment and comparative example and stick it on a copper tape, and use XPS to test the content of C and F elements on the adhesive surface.
[0122] 2. Solid electrolyte membrane stress-strain curve test: The solid electrolyte membrane obtained in the embodiment and the comparative example is cut into a regular rectangle, the sample is fixed on a universal material testing machine, and the solid electrolyte membrane is stretched at a speed of 1 cm / min until it breaks, and the stress and strain values of the solid electrolyte membrane when it breaks are obtained.
[0123] 3. Lithium ion conductivity test of solid electrolyte membrane: The solid electrolyte membrane obtained in the embodiment and comparative example was cut into discs with a diameter of 10 mm, and stainless steel was used as the blocking electrode. Under a certain pressure, the mold battery was assembled, and the solid electrolyte membrane was subjected to an AC impedance test using an electrochemical workstation to obtain the ionic conductivity of the solid electrolyte membrane.
[0124] 4. Cycle life test of solid-state batteries: At room temperature of 25°C, in the test voltage range of 2.5V (discharge cut-off voltage) to 4.2V (charge cut-off voltage), at a charge and discharge current rate of 0.1C / 0.1C, the solid-state battery was subjected to the first week of charge and discharge test; then, the solid-state battery was charged and discharged for 3 weeks at current rates of 0.2C / 0.2C, 0.5C / 0.5C, 1C / 1C, and 2C / 2C; finally, the solid-state battery was charged and discharged at a current rate of 0.5C / 0.5C. When the discharge capacity of the solid-state battery reached 80% of the first cycle discharge capacity at the 0.5C rate, the test was stopped and the number of cycles at room temperature was recorded.
[0125] Table 1: Examples 1 to 14 and Comparative Examples 1 to 4 provide stress strain and ionic conductivity test results of solid electrolyte membranes
[0126]
[0127] Table 2: Test results of cycle life of solid-state batteries provided by Examples 1 to 14 and Comparative Examples 1 to 4
[0128]
[0129] By comparing the test results of Examples 1 to 9 and Comparative Example 1, it can be seen that after the binder in the solid electrolyte membrane is treated with plasma, the C / F molar ratio on the binder surface will increase, and the O and N elements introduced after the plasma etching treatment on the binder surface form new active groups, which will increase the surface free energy of the binder and enhance the adhesion of the binder. Under the condition of ensuring that the ionic conductivity is not significantly attenuated, the mechanical strength of the solid electrolyte membrane is improved, thereby further improving the cycle life of the solid-state battery.
[0130] By comparing the test results of Examples 1 to 9 and Comparative Examples 1 to 2, it can be seen that limiting the C / F molar ratio of the modified binder surface to a suitable range of 0.41 to 1, especially when the C / F molar ratio is 0.41 to 0.88, can take into account the improvement effect of the ionic conductivity and mechanical strength of the solid electrolyte membrane, thereby improving the cycle performance of the solid-state battery. If the C / F molar ratio of the binder surface is too low (<0.41), the surface properties of the binder do not change much, only a small amount of F atoms are separated from the binder surface and only a small amount of new active groups are formed, and the lithium electron conductivity and mechanical strength of the prepared solid electrolyte membrane are not significantly improved; if the C / F molar ratio of the binder surface is too high (>1), the binder surface is too rough and difficult to fiberize, resulting in a decrease in the mechanical strength of the prepared solid electrolyte membrane.
[0131] By comparing the test results of Examples 6, 11 to 13 and Comparative Examples 3 and 4, it can be seen that limiting the mass ratio of sulfide electrolyte to binder in the solid electrolyte membrane to (90-99.5): (0.5-10) can make the solid electrolyte membrane have both good ionic conductivity and mechanical strength, thereby achieving the best effect of improving the cycle life of the solid-state battery. Among them, when the mass content of the binder in the solid electrolyte membrane is too low (<0.5%), the ionic conductivity of the solid electrolyte membrane is close to that of the sulfide electrolyte powder, but the solid electrolyte membrane has poor film forming properties or is difficult to form, making it impossible for the assembled battery to achieve charge and discharge cycles. As the mass content of the binder increases, too much binder in the solid electrolyte membrane is coated on the surface of the sulfide electrolyte particles, resulting in the obstruction of ion transmission between the sulfide electrolyte particles by mutual contact, causing the ion conductivity of the solid electrolyte membrane to decrease; in particular, when the mass content of the binder in the solid electrolyte membrane is too high (>10%), the binder in the solid electrolyte membrane is coated on the surface of the sulfide electrolyte, causing the ion conductivity of the solid electrolyte membrane to drop below 0.1mS / cm, making it impossible to conduct lithium ions between the positive electrode sheet and the negative electrode sheet.
[0132] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A solid-state battery, characterized in that: The invention comprises a solid electrolyte membrane, wherein the solid electrolyte membrane comprises a sulfide electrolyte and a binder, wherein the binder comprises at least one of a monomer, a dimer and a polymer containing fluorine, and the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41-1.
2. The solid-state battery according to claim 1, characterized in that: The molar ratio of carbon element to fluorine element on the surface of the binder is 0.41-0.
88.
3. The solid-state battery according to claim 1, characterized in that: The thickness of the solid electrolyte membrane is 30-60 μm.
4. The solid-state battery according to claim 1, characterized in that: The binder includes at least one of polytetrafluoroethylene, polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene, polyvinylidene fluoride-hexafluoropropylene copolymer and ethylene-tetrafluoroethylene copolymer.
5. The solid-state battery according to claim 1, characterized in that: The mass of the sulfide electrolyte is 90% to 99.5% of the mass of the solid electrolyte membrane; the mass of the binder is 0.5% to 10% of the mass of the solid electrolyte membrane.
6. The solid-state battery according to claim 1, characterized in that: The ionic conductivity of the sulfide electrolyte is greater than 1 mS / cm; and / or the particle size of the sulfide electrolyte is 1 to 10 μm.
7. The solid-state battery according to claim 1 or 6, characterized in that: The sulfide electrolyte includes Li3PS4, Li7P3S 11 , Li 10 GeP2S 12 , Li 10 SnP2S 12 , Li6PS5Br, Li6PS5Cl and Li 5.5 PS 4.5 Cl 1.5 At least one of .
8. A method for preparing a solid-state battery, characterized in that: include: Provide positive electrode sheets, solid electrolyte membranes and negative electrode sheets; Assembling the positive electrode plate, the solid electrolyte membrane and the negative electrode plate into a battery cell, and encapsulating the battery cell to obtain a solid-state battery; Wherein, the preparation method of the solid electrolyte membrane comprises: Providing a sulfide electrolyte and a binder, wherein the binder includes at least one of a monomer, a dimer, and a polymer containing fluorine; Modifying the surface of the binder so that the molar ratio of carbon element to fluorine element on the surface of the binder is 0.41 to 1; The sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane.
9. The preparation method according to claim 8, characterized in that: The binder is subjected to surface modification, comprising: Plasma etching is performed on the surface of the binder to remove fluorine atoms on the surface of the binder and generate free radicals; The binder is exposed to a doping source gas, so that the doping elements in the doping source gas are combined with free radicals on the surface of the binder to form active groups; the doping elements include nitrogen and / or oxygen.
10. The preparation method according to claim 8, characterized in that: The sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane, comprising: The sulfide electrolyte and the binder are mixed to form a solid electrolyte membrane by wet coating or dry extrusion; wherein the mass ratio of the sulfide electrolyte to the binder is (90-99.5):(0.5-10).
Citation Information
Patent Citations
Method for producing separator, method for producing molten salt battery, separator, and molten salt battery
CN102834949A
Binder, slurry for solid-state battery, electrode for solid-state battery, and solid-state secondary battery
CN114207881A
Polyvinylidene fluoride dispersion liquid, preparation method thereof and composite diaphragm
CN116814023A
Lithium ion secondary battery and its manufacture
CN1245592A
Negative electrode, battery, and their manufacturing method
JP2006134682A
Cited By
Positive electrode for all-solid-state battery, and all-solid-state battery comprising same
WO2026197471A1